Possible causes of early mortality of individual microentre-preneurs and micro and small companies (Revista Brasileira de Contabilidade e Gestão, 2022)
The objective of this article was to identify possible causes of mortality of small businesses and individual micro-entrepreneurs in the municipality of Palmas - Paraná, between 2015 and 2020. This study was developed through descriptive research, with survey, analysis of secondary data, and documental bibliographic research of literature. To this end, a study was carried out with managers of individual micro-enterprises and small companies that ended their activities early. The results obtained suggest that there is a set of factors and not just one in isolation, as the possible cause of the early mortality of small businesses in the municipality, highlighting: the lack of adequate business planning, market study, interest rates high, lack of business knowledge, experience, strategy, identification with the business, bureaucracy and lack of support from specialized bodies.
Keywords: entrepreneurship; innovation; business planning; individual microentrepreneur; micro and small companies; strategic planning